TANZİMAT ŞİİRİNDE METAFİZİK KONULAR: ŞİNASİ, ZİYA PAŞA, NAMIK KEMAL, RECAİZADE M. EKREM, ABDÜLHAK HAMİD, MUALLİM NACİ - AYAZ, HAYRETTİN (Fırat Üniveristesi, 1995)
Turkish Literature under the influence of European thought that was approximately began 20 years after the "Tanzimat Fermanı" which determines the beginning of radical transformations on social and political areas in the last 150 years of our history, has been made research subject many ways up to date. But, our analysis in this research is based on the work of the six prominent poets, namely Şinasi, Ziya Paşa, Namık Kemâl, Recâizâde Mahmud Ekrem, Abdülhak Hâmid and Muallim Naci. The reason of limitation of this study with six poets is their representation the charactaristic of the Tanzimat poetry. The basic determinant that gives important chartaristics to the metaphysic theme of the Tanzimat poetry is certainly philosophical and theological points. On this occasion we tried to discuss the metaphysic dimension of the Tanzimat Poetry by using some terms (Theology, ontology, cosmology, agnosticism etc.) in this research.
Metaphysic themes of Tanzimat poetry
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır.Yayınlanma izni olmayan tezlerin basılı kopyalarına üniversite kütüphaneniz aracılığı ile (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature